الحاجات الإرشادية للتلميذ العدواني بالمرحلة الثانوية - بلعربي, جموعي; خنيش, يوسف (My University, 2020)
ملخص: تسعى هذه الدراسة إلى كشف الحاجات الإرشادية للتلميذ العدواني بالمرحلة الثانوية والمتعلقة بالمجال النفسي والاجتماعي والتربوي. تم الاعتماد على المنهج الوصفي من خلال بناء استبيان تقدير الحاجات الإرشادية والذي يحتوى على 39 عبارة موزعة على المحاور الثلاثة. والذي تم توزيعه على عينة الدراسة التي يبلغ عددها 34 تلميذا عدوانيا بالمرحلة الثانوية على مستوى ثانويات سيدي عقبة بسكرة. خلصت نتائج الدراسة إلى حصر مجموعة من الحاجات الإرشادية للتلاميذ العدوانيين حيث كانت معظم حاجاتهم تنتمي إلى المجال النفسي والاجتماعي والتي جاءت استجابة عينة الدراسة عليها بدرجة كبيرة. وأوصت الدراسة بضرورة الاهتمام بإشباع الحاجات النفسية والاجتماعية والتربوية للتلميذ المراهق لتحقيق تكيف جيد والمساهمة في الحد من السلوك العدواني. Abstract: This study aims at identifying the indicative needs of the aggressive student in the secondary level that is related to the psychological, social and educational field. The descriptive approach was adopted, based on constructing a questionnaire of the indicative needs assessment, that contains 39 words distributed on the three axes, This questionnaire was distributed to the study sample of 34 aggressive students of secondary level at the secondary schools of SidiOkba,The results of the study concluded that a set of extension needs of aggressive students were identified, where most of their needs were in the psychosocial field, which was highly responsive to the study sample; The study recommended the need to pay attention to satisfying the psychological, social and educational needs of the adolescent student to achieve good adaptation and contribute to the reduction of aggressive behavior.
مقال
Keywords: حاجات ; حاجات إرشادية ; سلوك عدواني ; تلميذ ; مرحلة ثانوية; needs; Instructional needs; Aggressive behavior; Student; Secondarylevel.